Arsenate Removal from Water by Simultaneous Green Tea Nano-Zerovalent Iron and Ultrasonic Wave. (9th April 2014) - Ashouri, Abolfazl; Anvaripour, Bagher; Motavassel, Mohsen; Jaafarzadeh Haghighifard, Nematolah
Abstract : Nano-zerovalent iron (NZVI) was synthesized using green tea (GT) extract and it was used as an adsorbent in arsenate removal from water. FESEM, PSD, and XRD employed in the examination of particles and their characterizations. Results showed that the particles were spherical lumped together in a texture structure with sizes ranging from 20 to 70 nanometers. All experiments were accomplished in a batch mode. Adsorption isotherm, adsorption kinetics, and the effects of pH, GT-NZVI dosage, and ultrasonic wave power on arsenate separation capabilities were explored. The results suggested that the arsenate removal efficiency enhanced with increasing GT-NZVI dosage. Increase in pH from 3 to approximately 6 leads to increase in the removal efficiency; however, increasing the pH further decreased the removal efficiency. The effect of ultrasonic power on As(V) removal was dependent on pH and NZVI dosages. The positive effect was more pronounced at low adsorbent dosages and acidic solution in which the As(V) removal efficiency improved with increasing ultrasonic power. However, in highly alkali solutions As(V) removal efficiency reduced with increasing ultrasonic power. The adsorption kinetics followed second order, while the adsorption isotherm was fitted best with Langmuir equation at a maximum capacity of 34.2 mg g −1 .